In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol. Issue 23 (1st December 2020) - Freitas, Jolindo A.; Sorrechia, Rodrigo; Politi, Flávio A. S.; Santos, André G.; Rodrigues, Edvânio R.; Santos, Lourdes C.; Fusco-Almeida, Ana M.; Oliveira, Andrew A.; Guido, Rafael V. C.; Pietro, Rosemeire C. L. R.
Abstract: Dermatophytosis is a dermic disease caused by fungi. The aim of this study was to search anti-dermatophyte bioactive compounds in Piper umbellatum leaves. Cytotoxicity evaluation was performed against MRC-5 and HepG2 as a selectivity parameter. Crude ethanol extract presented MIC value of 39.1 μg/mL against M. canis and no cytotoxicity to Hep G2 (human liver cancer) and MRC-5 (normal lung fibroblast). 4-nerolydilcatechol was isolated from P. umbellatum ethanolic extract. MIC values for 4-NC were 7.6μM to M. canis and 15.6μM to Trichophyton rubrum. 4-NC presented activity against M. canis 14 times lower than to MRC-5 (non-tumoral human cell line), which suggest selective activity for this fungus. Molecular modeling suggests 4-NC could bind to CYP51, present in lanosterol synthesis, blocking fungi development. In conclusion, P. umbellatum crude ethanol extract and 4-NC demonstrated high and selective in vitro antifungal activity.